Surgical Site Infections: Epidemiological, Clinical and Bacteriological Aspects in the Urology Department of the Regional Hospital of Saint-Louis - Lo, Seynabou; Khadim, Niang; Bambo, Diakhaby Mba El Hadji; Issa, Thiam; Ahmet, Niang Aissatou; Habibou, Sarr; Fatoumata, Diallo (British Journal of Healthcare and Medical Research, 2022)
Introduction: Surgical site infections occur within 30 days or one year after operation. They are important factors of morbidity and mortality in surgery, with a significant economic impact especially in developing countries. In sub-Saharan Africa, rate is estimated between 6.8-26% and 3.36% in Senegal. The objective of this study was to evaluate SSI in urology of Regional Hospital of Saint-Louis and study bacteria isolated. Material and Method: A prospective, descriptive and analytical study was conducted in urology department with patients operated on and hospitalized from february 2019 to january 2020 and who presented suppuration of surgical site. Samples were taken by swabbing wound or by puncture. Microbiology examination was done by microscopic, culture and identification of bacteria who were tested with antibiotics according to the CA-SFM 2019. Data entry was done with Excel 2019 and analysed by SPSS version 22. Results : 134 patients were concerned witch mean of age 49.69 years and the most risk factors were hypertension (23.88%), and diabetes (5.97%). Stage I (70.90%) of ASA and stage I (37.31%) of Altemeier were predominant. Eighteen patients (13.43%) had an SSI and 27 bacterial strains were isolated with predominance of enterobacteria (81.5%). Six isolates produced extended spectrum beta-lactamase with multi-resistant bacteria associated by longer hospital stay. Conclusion: Surgical Site Infections are a real factor of morbidity and mortality in surgery. In addition, increasing emergence of antibiotic-resistant makes treatment more difficult. It is urgent to set up a system of coordinated control of these SSI and all action undertaken must be multidisciplinary.